Urban Size and Labor Market Premium: Evidence from Indonesia - Msy Nourma Yunita Sari; Muhammad Halley Yudhistira (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2023)
The study of economic agglomeration is again a concern in the urban economic literature, especially in describing urban areas and better econometric approaches. This study improves the size of cities to become urban and suburban, reflecting the flow of commuting, using the 2010 and 2015 Landscan data to measure economic density better and reduce bias due to measurement errors. Empirically, using this density and using the 2SLS estimation technique with instrument variables in the form of earthquake risk and ruggedness measures, the result of a city twice as large can increase wages 61 percent. This result is higher than most other literature because the sample only covers urban areas. This study also shows that workers with characteristics such as higher education, the formal sector, the service sector, and white collar jobs get more enormous benefits in urban areas.JEL Classification: J24, J31, O18How to Cite:Sari, M. N. Y., & Yudhistira, M. H. (2023). Urban Size and Labor Market Premium: Evidence from Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 12(1), 27-44. https://doi.org/10.15408/sjie.v12i1.27999.